Search for supersymmetry in pp collisions at √s = 7 TeV in final states with missing transverse momentum and b-jets - Anduaga, Xabier Sebastián (2011)
Results are presented of a search for supersymmetric particles in events with large missing transverse momentum and at least one heavy flavour jet candidate in √s = 7 TeV proton–proton collisions. In a data sample corresponding to an integrated luminosity of 35 pb-1 recorded by the ATLAS experiment at the Large Hadron Collider, no significant excess is observed with respect to the prediction for Standard Model processes. For R-parity conserving models in which sbottoms (stops) are the only squarks to appear in the gluino decay cascade, gluino masses below 590 GeV (520 GeV) are excluded at the 95% C.L. The results are also interpreted in an MSUGRA/CMSSM supersymmetry breaking scenario with tan β = 40 and in an SO(10) model framework.